Risk factors that influence clavicle fracture in the newborn babies of vaginal delivery occurred in obstetrical center of the Maternal Perinatal National Institute in the period 2011 - admin, admin (2018)
Objectives. Identify the risk factors that influence clavicle fracture in newborn babies of vaginal births. Material and methods. Retrospective, descriptive, observational study. Data of the stories were collected clinics for women whose vaginal birth was attended in the Obstetrical Center of the Maternal Perinatal National Institute during the period from January to december 2011, and whose newborn had diagnostic radiology clinical of clavicle fracture. Results. A total of 8441 vaginal births there were 169 fractures of clavicle in the newborn, representing a prevalence of 2%. Of 169 cases studied, 50,8 per cent correspond to primiparous women and 7,2% to large multiparous. Also, 17,8% and 17,2% occurred in adolescents and old mothers respectively. As maternal background, 68,6% had previous caesarean section and 56,8% no antenatal care. According to gestational age 98,2% are preterm newborns at term and 1,78%. In relation to the weight infants, 91,7% correspond to appropriate weight at birth and 7,5% were macrosomics. The right collarbone broke in 59,8% while 40,2 per cent corresponded to the left side. 74,6% of cases were attended by midwives, followed 20,1% by attending physicians and 5,3% by medical residents. Conclusions. Suggest us that the clavicle fracture of the newborn is common in adolescents, old, mothers primiparous women without prenatal care, previous caesarean and newborn term with appropriate weight at birth.